2013
DOI: 10.2460/javma.242.11.1523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body position on indirect measurement of systolic arterial blood pressure in dogs

Abstract: Blood pressure measurements in dogs were significantly affected by body position, and they were higher for most dogs when sitting rather than laterally recumbent. Blood pressure measurements in the laterally recumbent body position were less variable than in the sitting position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…18 A recent study reported a significantly higher mean SBP and less repeatable measurements in dogs in a sitting positing compared with lateral recumbency. 56 Although the position could be a cause for some of the increased measurements in our study, the fact that these animals did not tolerate recumbency could also indicate more stress.…”
Section: Discussionmentioning
confidence: 75%
“…18 A recent study reported a significantly higher mean SBP and less repeatable measurements in dogs in a sitting positing compared with lateral recumbency. 56 Although the position could be a cause for some of the increased measurements in our study, the fact that these animals did not tolerate recumbency could also indicate more stress.…”
Section: Discussionmentioning
confidence: 75%
“…Several previous studies have also identified discordance between indirect and direct blood pressure measurements taken at different sites (Bodey & Michell, 1996; Rondeau, Mackalonis & Hess, 2013; Acierno et al, 2015). Bodey & Michell (1996) found oscillometric systolic blood pressure measurements were significantly lower at the coccygeal artery compared to the radial artery in standing dogs.…”
Section: Discussionmentioning
confidence: 94%
“…This could have led to a greater discrepancy in results than would have been observed had the dogs all been positioned in sternal recumbency for coccygeal readings. The impact of body position on indirect blood pressure measurement is further highlighted by the results of Rondeau, Mackalonis, and Hess, in which the mean SAP in conscious dogs measured on the forelimb was significantly higher in the sitting position than in lateral recumbency (Rondeau, Mackalonis & Hess, 2013). Finally, significant differences have been noted in direct SAP measurements collected at different anatomic sites, particularly at the carpus and hindlimb (Acierno et al, 2015), suggesting an anatomic basis for discordance in pressures at different sites.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Blood pressure measurement results in normal animals are highly variable based on breed, temperament, patient position, measurement method, operator experience, and intrapatient variability, and it is difficult to determine a single value and range that might be applicable to all dogs or cats. Ranges of expected values in many studies of normal dogs and cats using various measurement techniques are presented in Table .…”
Section: Normal Values For Canine and Feline Bpmentioning
confidence: 99%